EXPERIENCE OF LOCAL ZONING OF CULTURAL LANDSCAPES OF THE NORTH CAUCASUS - Alexey Vladimirovitsh Lysenko; Daria Sergeevna Vodopyanova; Dmitry Sergeevitsh Azanov (Наука. Инновации. Технологии)
This paper deals with the theoretical and methodological problems of cultural landscape regionalization mikrogeograficheskom level research. As an example, the traditional IP-toric cultural landscape Stavropol Turkmen, urban cultural landscape of the city of Stavropol, the Terek-Malkinskiy boundary cultural landscape of the North Caucasus Frontier and Alexander novation rural cultural landscape